Interinstitutional beam model portability study in a mixed vendor environment. Issue 12 (13th October 2021) - Frigo, Sean P.; Ohrt, Jared; Suh, Yelin; Balter, Peter
Abstract: A 6 MV flattened beam model for a Varian TrueBeamSTx c‐arm treatment delivery system in RayStation, developed and validated at one institution, was implemented and validated at another institution. The only parameter value adjustments were to accommodate machine output at the second institution. Validation followed MPPG 5.a. recommendations, with particular attention paid to IMRT and VMAT deliveries. With this minimal adjustment, the model passed validation across a broad spectrum of treatment plans, measurement devices, and staff who created the test plans and executed the measurements. This work demonstrates the possibility of using a single template model in the same treatment planning system with matched machines in a mixed vendor environment.